THE STUDENTS’ ATTITUDE OF USING BLOOKET AS A GRAMMAR LEARNING MEDIA - Fitri Amalia; Syafryadin (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
Although blooket is a game-based learning tool extensively investigated for vocabulary acquisition, its application in grammar education is yet understudied. This study sought to find how students attitudes about applying Blooket for grammatical instruction. One hundred and fifty-six ninth-grade students from SMP Negeri Karang Jaya were selected through purposive sampling during the 2024–2025 academic year. A 17-item questionnaire was distributed using Google Forms to gather the data. The survey concentrated on three critical components: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Behavioral Intention (BI). The results indicated generally positive student responses. The mean scores were relatively high, PU (4.26), PEOU (4.24), and BI (4.28) suggesting that students believed Blooket as a useful and engaging tool for learning grammar. Students were eager to utilize Blooket for grammar drills, confident, and motivated. Features like quick feedback and leaderboards enhanced the enjoyment of the experience. The study shows how game-based platforms like Blooket can get students more interested in learning and encourage them to engage more. Finally, the results show that Blooket is more enjoyable and useful way to learn grammar. This aligns with the current educational goals of using technology and game-like elements in teaching.